PENGARUH PROFITABILITAS, STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL SEKTOR CONSUMER NON-CYCLICALS - Handayani, Dewi Sri; Fandil, Fandil; Rochmawan, Mohammad Laksono Tri (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
The capital structure is a description of the company's finances for sources of financing by calculating the difference between own capital and long-term debt. The purpose of this study is to determine the factors that influence the capital structure of Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange in 2019-2021. The population in this study were all Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange totaling 57 companies. The sample in this study used purposive sampling so that a sample of 30 companies was obtained. The dependent variable in this study is Capital Structure, the independent variables are Profitability (X1), Capital Structure (X2) and Firm Size (X3). The analytical method uses multiple linear regression analysis. Based on the results of data analysis it was concluded that Profitability has no effect on Capital Structure with a significance value of 0.137 > 0.05. Asset structure has no effect on capital structure with a significance value of 0.667 > 0.05. Firm size has an effect on Capital Structure with a significance value of 0.004 <0.05. The coefficient of determination is 8.8%. Advice that can be given to investors is to pay attention to the Company Size ratio because it affects the Capital Structure of the company, so that investment will be more profitable. For future researchers to be able to replace or add other types and sectors so that more accurate results are obtained.